The CsrA-FliW network controls polar localization of the dual-function flagellin mRNA in Campylobacter jejuni - Gaurav Dugar (Nature Portfolio, 2016)
The CsrA protein binds to and represses translation of certain bacterial mRNAs. Here, Dugar et al. show for the human pathogen Campylobacter jejunithat the major flagellin mRNA acts as both a target and a regulatory 'sponge' for CsrA, and is localized at the cell poles in a translation-dependent manner.